Концептуальні аспекти управління розподілом медичного майна з позиції військово-фармацевтичної логістики - Білоус, М. В.; Шматенко, О. П; Рижов, Олексій Анатолійович; Трохимчук, В. В.; Галан, О. В.; Дроздов, Д. В.; Белоус, М. В.; Шматенко, А. П.; Рыжов, А. А.; Трохимчук, В. В.; Галан, А. В.; Дроздов, Д. В.; et al. (My University, 2019)
Одним з основних напрямів логістичного забезпечення Збройних Сил України є медичне забезпечення, яке спрямовано на збереження життя і здоров’я військовослужбовців, своєчасне та ефективне надання медичної допомоги у разі поранень, уражень і захворювань, якнайшвидше відновлення боєздатності та працездатності в різних умовах їх застосування та в різні періоди часу. Готовність медичної служби Збройних Сил України до медичного забезпечення військ безпосередньо залежить від своєчасної організації медичного постачання та поповнення медичного майна в повному обсязі. Визначальне місце в цьому процесі займає якісний та ефективний розподіл медичної техніки та медичного майна. Мета роботи – обґрунтування особливості розподільчої логістики у єдиній системі логістичного забезпечення Збройних Сил України та вивчення основних аспектів управління розподілом медичної техніки і майна з позиції військово-фармацевтичної логістики. Для досягнення мети дослідження проведено аналіз вітчизняних наукових джерел та діючої нормативно-правової бази України. Методами дослідження є інформаційний пошук, порівняння, систематизація, семантичний аналіз, синтез та моделювання. В умовах логістичного забезпечення Збройних Сил України та інших складових сил безпеки і оборони України, логістична функція з розподілу матеріально-технічних засобів, озброєння, військової техніки та послуг (харчування, лазне-пральне обслуговування тощо) має забезпечити діяльність військ (сил) у мирний та воєнний час. Це, в свою чергу, є запорукою здатності гарантовано забезпечити оборону держави та адекватного реагування на воєнні загрози національній безпеці України, раціонально використовуючи при цьому наявний потенціал та ресурси. Розподільча логістика з позиції військово-фармацевтичної логістики – це управлінням всіма функціональними підсистемами закладів медичного постачання і охорони здоров’я Міністерства оборони України з метою оптимізації розподілу матеріального потоку (закупленого медичного майна) від постачальника до кінцевого споживача (за заявками Військово-медичних клінічних центрів регіонів). Проведено дослідження з обґрунтування особливості розподільчої логістики у єдиній системі логістичного забезпечення Збройних Сил України та вивчено основні аспекти управління розподілом медичної техніки і майна з позиції військово-фармацевтичної логістики. Запропоновано замінити термін «збутова логістика» на «розподільча логістика» у зв’язку з неможливістю його використання як у єдиній системі логістичного забезпечення Збройних Сил України, так і в її підсистемах. Отже, розподільча логістика у структурі єдиної системи логістичного забезпечення Збройних Сил України не несе комерційної складової, а її функції полягають у плануванні, організації розподілу, контролю і регулюванню логістичного процесу розподілу матеріально-технічних засобів (в т. ч. медичної техніки та майна), озброєння, військової техніки, послуг (харчування, лазне-пральне обслуговування тощо). Побудовано модель діючого логістичного ланцюга розподілу медичної техніки та майна в Збройних Силах України. Встановлено, що для забезпечення якісного та ефективного розподілу медичної техніки та майна необхідно створення нормативно-правової бази, яка б регламентувала розподіл повноважень між закладами і підрозділами медичного постачання Міністерства оборони України та визначала відповідальність за їх виконання в сучасних умовах реформування Збройних Сил України.

Одним из основных направлений логистического обеспечения Вооруженных Сил Украины является медицинское обеспечение, которое направлено на сохранение жизни и здоровья военнослужащих, своевременное и эффективное оказание медицинской помощи в случае ранений, поражений и заболеваний, скорейшее восстановление боеспособности и работоспособности в различных условиях и в разные периоды времени. Готовность медицинской службы Вооруженных Сил Украины к медицинскому обеспечению войск напрямую зависит от своевременной организации медицинского снабжения и пополнения медицинского имущества в полном объёме. Определяющее место в этом процессе занимает качественное и эффективное распределение медицинской техники и медицинского имущества. Целью работы было обоснование особенности распределительной логистики в единой системе логистического обеспечения Вооруженных Сил Украины, а также изучение основных аспектов управления распределением медицинской техники и имущества с позиции военно-фармацевтической логистики. Для достижения цели исследования проведен анализ отечественных источников научной литературы и действующей нормативно-правовой базы Украины. Методами исследования являются информационный поиск, сравнение, систематизация, семантический анализ, синтез и моделирование. В условиях логистического обеспечения Вооруженных Сил Украины и других составляющих сил безопасности и обороны Украины, логистическая функция по распределению материально-технических средств, вооружения, военной техники и услуг (питание, банно-прачечное обслуживание и т. п.) должна обеспечить деятельность войск (сил) в мирное и военное время. Это, в свою очередь, является залогом способности гарантированно обеспечить оборону государства и адекватного реагирования на военные угрозы национальной безопасности Украины, рационально используя при этом имеющийся потенциал и ресурсы. Распределительная логистика с позиции военно-фармацевтической логистики – это управление всеми функциональными подсистемами учреждений медицинского снабжения и здравоохранения Министерства обороны Украины с целью оптимизации распределения материального потока (закупленного медицинского имущества) от поставщика до конечного потребителя (по заявкам Военно-медицинских клинических центров регионов). Проведено исследование по обоснованию особенности распределительной логистики в единой системе логистического обеспечения Вооруженных Сил Украины и изучены основные аспекты управления распределением медицинской техники и имущества с позиции военно-фармацевтической логистики. Предложено заменить термин «сбытовая логистика» на «распределительная логистика» в связи с невозможностью его использования как в единой системе логистического обеспечения Вооруженных Сил Украины, так и в её подсистемах. Таким образом, распределительная логистика в структуре единой системы логистического обеспечения Вооруженных Сил Украины не несёт коммерческой составляющей, а её функции заключаются в планировании, организации распределения, контроле и регулировании логистического процесса распределения материально-технических средств (в том числе медицинской техники и имущества), вооружения, военной техники, услуг (питание, банно-прачечное обслуживание и т. п.). Построена модель действующей логистической цепи распределения медицинской техники и имущества в Вооруженных Силах Украины. Установлено, что для обеспечения качественного и эффективного распределения медицинской техники и имущества необходима нормативно-правовая база, регламентирующая распределение полномочий между учреждениями и подразделениями медицинского снабжения Министерства обороны Украины и определяющая ответственность за их выполнение в современных условиях реформирования Вооруженных Сил Украины.

One of the main directions of logistic support of the Armed Forces of Ukraine is medical support which is aimed at life safeguard and health of military personnel, well-timed and efficient provision of medical care in the event of injuries, injuries and diseases, fast renewal of combat power and ability to work in different conditions of its handling and at different period of time. The readiness of medical service of the Armed Forces of Ukraine to the medical support of the troops depends on the well-timed organization of medical supplies and the refilling of medical supplies full and complete. The qualitative and efficient allocation of medical equipment and medical supplies is a determining factor in this process. The aim of the work – reasoning of the irregularity of distribution logistics in the unified logistic system of the Armed Forces of Ukraine and the study of the main aspects of management of the distribution of medical supplies from the position of military pharmaceutical logistics. To get the purpose of the research, the analysis of domestic scientific sources and the current normative and legal base of Ukraine have been carried out. Research methods are: information search, comparison, systemization, semantic analysis, synthesis and modeling. In the conditions of logistic support of the Armed Forces of Ukraine and other components of the security and defense forces of Ukraine, the logistic function of the distribution of logistical equipment, inventory, military equipment and services (food, bath and laundry services, etc.) should ensure the activity of troops (forces) in peacetime and war time. It is the guarantee of the ability to ensure the defense of the state and appropriate response to military threats to the national security of Ukraine, efficiently using available potential and resources. Distribution logistics from the position of military pharmaceutical logistics is the management of all functional subsystems of the medical supplies and health services of the Ministry of Defense of Ukraine in order to optimize the distribution of the material flow (purchased medical supplies) from the supplier to the final consumer (according to the applications of the Military Medical Clinical Centers of the Regions). Same, distributive logistics in the structure of a unified logistic support system of the Armed Forces of Ukraine does not carry a commercial component, and its functions consist in planning, organization of distribution, control and regulation of the logistic process of distribution of material and technical means (including medical equipment and supplies), inventory, military equipment, services (catering, bath and laundry service, etc.). According to the authors, the term «marketing logistics» is not possible to use as a single system of logistic support of the Armed Forces of Ukraine, and in its subsystems. To sum it up, it was suggested to use the term «distributive logistics». On the basis of theoretical generalization of the data of scientific literature and normative legal acts, the main aspects of management of the distribution of medical equipment and supplies from the standpoint of military pharmaceutical logistics are studied. The functions of distributive logistics are defined, the model of the current logistic chain of distribution of medical equipment and supplies in the medical service of the Armed Forces of Ukraine is constructed. It is noted that in order to ensure the qualitative and efficient distribution of medical equipment and supplies, a regulatory and legal framework which regulates the division of powers between institutions and units of medical supplies and defines the responsibility for their implementation in the current conditions of the reformation of the Armed Forces of Ukraine.
Концептуальные аспекты управления распределением медицинского имущества с позиции военно-фармацевтической логистики
Conceptual aspects of management of the distribution of medical supplies from the position of military pharmaceutical logistics
Keywords: військова логістика; військово-фармацевтична логістика; військово-медичне постачання; військова фармація; военная логистика; военно-фармацевтическая логистика; военно-медицинское снабжение; военная фармация; military logistics; military pharmaceutical logistics; military medical supply; military pharmacy